EMPLOYEE PERFORMANCE IMPROVEMENT MODEL BASED ON ISLAMIC WORK BEHAVIOR TO THE UMKM BATIK EMPLOYEES - Faizal Widya Kusuma (IJIBE (International Journal of Islamic Business Ethics), 2018)
This study aims to describe and analyze the effect of education, training and work experience on Islamic work behavior and its impact on human resource performance. The population used is employeesof batik UMKM in Central Java region. Based on the questionnaire distribution of 100 respondents, responded by the employees of 88 employees. The sampling technique is simple random sampling. Theanalysis tool is multiple linear regression, where previously tested the validity and reliability as well as the classical assumption test. The result of the test shows that education on Islamic work behavior shows a positive influence, it can be interpreted that the higher level of education owned by employees, it will increasingly increase the change of attitude and employee’s Islamic work behavior. Similarly,training and work experience also proved to have a positive effect on the behavior of Islamic work. Islamic behavior is proven to have a positive influence on the performance of human resources, can beinterpreted that the higher the ability of employees in making changes in attitudes and behavior of Islamic behavior, it will further improve the performance of human resources.Keywords: Education, training, work experience, Islamic work behavior and human resource performance